2017
DOI: 10.1590/1980-5373-mr-2017-0101
|View full text |Cite
|
Sign up to set email alerts
|

On The Mechanical Behavior of Metakaolin Based Geopolymers Under Elevated Temperatures

Abstract: Geopolymers may be described as solid and stable synthesized aluminosilicate materials, whose properties are generally believed to provide a superior durability behavior. The work in hand presents the results of an experimental investigation on the thermomechanical behavior of geopolymer matrices composed by metakaolin (MK), silica fume (SF) and blast furnace slag (BFS). The alkaline activator solution consisted of sodium silicate and sodium hydroxide. The use of different aggregates was also investigated, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 10 publications
3
11
1
1
Order By: Relevance
“…The addition of fillers mitigates the shrinkage of the geopolymer binders (the material does not crack due to heating). The results indicate decreases in compressive strength of geopolymer composites with increasing temperature, which were also previously published [23,25,30,47,56]. A slight increase in compressive strength after exposure to 200 • C was observed with GC, GS, and GR samples.…”
Section: Mechanical Propertiessupporting
confidence: 87%
See 3 more Smart Citations
“…The addition of fillers mitigates the shrinkage of the geopolymer binders (the material does not crack due to heating). The results indicate decreases in compressive strength of geopolymer composites with increasing temperature, which were also previously published [23,25,30,47,56]. A slight increase in compressive strength after exposure to 200 • C was observed with GC, GS, and GR samples.…”
Section: Mechanical Propertiessupporting
confidence: 87%
“…Hemra et al [30] examined the geopolymer composite based on metakaolin and sodium activator with the addition of cordierite (30 wt %) and the compressive strength was 57.5 MPa at room temperature. Rovnaník et al [25,47] [23] also revealed a descending paths of compressive strength of geopolymer composites based on metakaolin and sodium activator with the addition of chamotte or quartz (50 wt %) with increasing temperature. The described results of compressive strength of geopolymer composites were 72 MPa for quartz and 62 MPa for chamotte at laboratory temperature and 7 MPa for quartz and 18 MPa for chamotte after the exposure to 1000 • C. The reason for the high values of compressive strength of the prepared geopolymer composites was probably the appropriate binder composition, especially its low viscosity, which made it possible to achieve a high fill rate (high content of filler in the composite) and thus excellent mechanical properties after thermal exposure.…”
Section: Mechanical Propertiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Geopolymers exhibit a fragile behavior with low deformation capacity as is typical of ceramics 10 . The use of reinforcements has been well explored in distinct forms to enhance their strength and ductility, such as additions of: sand 10 and chamotte 10‐12 as particulate reinforcements; as well as incorporations of synthetic (PVA, 13 PE, 14 carbon, 15 glass, 16 steel 9 ), mineral (basalt 11,17 ) and natural (bamboo, 18 jute, 8 sisal 19 ) fibers. Basalt fibers appear to be an interesting compatible material to be incorporated into geopolymer binders due to their high tensile strength, alkali resistance, 11 durability, and resistance to elevated temperatures 16 …”
Section: Introductionmentioning
confidence: 99%